Latin American Monetary Policy in the Pandemic Era - Steven B. Kamin; John Kearns (American Enterprise Institute (AEI), 2022)
This paper assesses Latin American monetary policy during the pandemic era against the benchmark of a "balanced" monetary policy strategy, that is, a strategy in which policies respond both to deviations of economic activity from equilibrium as well as deviations of inflation from target. We first review the evolution of Latin American monetary policy during this period. Central banks in the region cut rates sharply in response to the recession of 2020, despite steep currency depreciations, but subsequently tightened policy aggressively as inflation rebounded in 2021. We then compare these developments to the behavior of Latin American monetary policy in previous years. Estimating a Taylor rule for the period 2007 to 2019, we find that Latin American central banks had been responding in a balanced manner to movements in both inflation and output. However, with the pandemic, the weight of inflation in their reaction function rose substantially and the weight of output declined. Consistent with that finding, we find that policy interest rates generally fell less in 2020 than those predicted by the Taylor rule model (estimated over pre-pandemic years), and they rose more than predicted by the model in late 2021 and early 2022. Our findings could be interpreted to mean that Latin American central banks abandoned a balanced strategy in favor of one focused solely on fighting inflation. But we believe it more likely that the model, estimated over a more normal period, simply may not provide a good guideline for how Latin American central banks would (or should) react in response to a downturn of unprecedented depth followed by an equally dramatic inflationary surge. Several good reasons for monetary policy in the region to have tightened unusually sharply over the past year fall outside the scope of the standard Taylor rule, including the expansion of fiscal deficits and debt, the drag on supply from pandemic scarring, and the extraordinary rise in global interest rates.
Keywords: 330